PEMBAYARAN PAJAK BUMI DAN BANGUNAN; KASUS KABUPATEN PIDIE - Mariana, Mariana (HEI EMA : Jurnal Riset Hukum, Ekonomi Islam, Ekonomi, Manajemen dan Akuntansi, 2023)
The research objective is related to the practice of paying Land and Building Tax (PBB) in the revenue sector at the Pidie Financial Management Agency. The general aim of the research is to gain a better understanding, analyze, or improve the PBB payment process and its impact on the revenue sector of the Pidie Financial Management Agency. The research method used is qualitative, by conducting field research using interviews, documentation and observation. The research results show that Land and Building Tax (PBB) at the Pidie Financial Management Agency is regulated by Pidie Regency Qanun Number 1 of 2013. PBB is imposed on land and/or buildings, calculated based on the Sales Value of the Tax Object (NJOP) and the Sales Value of the Tax Object No Taxable (NJOPTKP). Collection is carried out manually by the Subdistrict PBB. Failure to pay PBB may result in sanctions, and tax collection rights expire after five years.